PENGARUH MOTIVASI, KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA (STUDI PADA PEGAWAI DI KECAMATAN PAKUSARI KABUPATEN JEMBER) - Sudarsih, Sudarsih (BISMA: Jurnal Bisnis dan Manajemen, 2016)
Abstract : The aim of this study was to identify and analyze the effect of motivation, leadership, and work environment to work performance of employee at Pakusari District Jember Regency. Thirty employees used as samples independent variables of this study were motivation, leadership, and work environment. While work performance was the dependent variable. The data collected was analyze by regression logistic method.The result of this study shows that motivation, leadership, and work environment has significantly effet to work performance of employee at Pakusari District Jember RegencyKeywords: Motivation, Leadership, Work environment, and work performance